The Current State of Educational Debt among Practicing Urologists. Issue 6 (25th November 2021) - Harris, Andrew M.; Langston, Josh; Webster, Joshua; Meeks, William; Fang, Raymond; North, Amanda
Abstract: Introduction: Previous studies have shown urology trainees to carry large amounts of educational debt. However, little is known about the educational debt metrics in the urology workforce. Therefore, we set out to characterize educational debt among practicing urologists. Methods: The American Urological Association (AUA) Workforce Workgroup examined the 2019 AUA Census data. Domains pertaining to demographics and educational debt were examined. Results: Of respondents 31.6% never had educational debt, 47.6% have paid off all their debt, 9.9% had ≤150, 000 debt, and 11% had >150, 000. Of the respondents practicing urology for 11–15 years since completing residency 20.2% had ≤150, 000 debt and 6.5% reported >150, 000 compared to 29% and 17.4%, respectively, for those practicing urology 6–10 years since completing residency. Of female urologists 18.6% had ≤150, 000 and 18.4% carried over >150, 000 compared to 9.0% and 10.1%, respectively, among male urologists (p <0.001). Concerning race, 21% of Black respondents carried ≤150, 000 and 30.4% carried >150, 000 compared to 9.4% and 10.9% in whites and 12.5% and 4.2% in Asian respondents. Furthermore, those in academic settings were more likely to have educational debt compared to those in private groups, 13.5% vs 10.7% vs 10.1% ≤150, 000 and 12.5% vs 10.9% vs 10.3% >150, 000, respectively (p=0.01); 23.6% felt their educational debt contributed to burnout Conclusions: A large percentage of practicing urologists carry educational debt for several years after residency. A higher percentage of respondents with Black race and female gender have debt compared to white and Asian race, and male gender. A substantial proportion of those with debt feel the debt contributes to burnout.